2015
DOI: 10.1016/j.euroneuro.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Short-term withdrawal from developmental exposure to cocaine activates the glucocorticoid receptor and alters spine dynamics

Abstract: Although glucocorticoid receptors (GRs) contribute to the action of cocaine, their role following developmental exposure to the psychostimulant is still unknown. To address this issue, we exposed adolescent male rats to cocaine (20mg/kg/day) from post-natal day (PND) 28 to PND 42 and sacrificed them at PND 45 or 90. We studied the medial prefrontal cortex (mPFC), a brain region that is still developing during adolescence. In PND 45 rats we found enhanced GR transcription and translation as well as increased tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 50 publications
3
18
1
Order By: Relevance
“…This hypothesis is corroborated by the evidence that the expression of PSD-95, an index of integrity and stability of excitatory synapses [27], is reduced in the mPFC but not Hip, in line with previous reports in humans [28]. Given that the reduced expression of PSD-95 might be suggestive of a reduced number of spines after repeated exposure to drugs of abuse [18], we hypothesize that ketamine has caused structural changes in this brain region that, together with reduced NMDA-mediated transmission, may contribute to the hypoglutamatergia observed in the post-mortem brains of schizophrenic patients [29,30]. This possibility is reinforced by the evidence that mGluR5 receptors, whose expression is reduced in the mPFC of ketamine-treated rats, regulate NMDA mediated cognitive functions [31] presumably via reduced activation of NMDA currents [32].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This hypothesis is corroborated by the evidence that the expression of PSD-95, an index of integrity and stability of excitatory synapses [27], is reduced in the mPFC but not Hip, in line with previous reports in humans [28]. Given that the reduced expression of PSD-95 might be suggestive of a reduced number of spines after repeated exposure to drugs of abuse [18], we hypothesize that ketamine has caused structural changes in this brain region that, together with reduced NMDA-mediated transmission, may contribute to the hypoglutamatergia observed in the post-mortem brains of schizophrenic patients [29,30]. This possibility is reinforced by the evidence that mGluR5 receptors, whose expression is reduced in the mPFC of ketamine-treated rats, regulate NMDA mediated cognitive functions [31] presumably via reduced activation of NMDA currents [32].…”
Section: Discussionsupporting
confidence: 88%
“…Our results show that ketamine-treated rats acquire and maintain the self-administration behavior suggesting that glutamate hypofunction is correlated to long-term ketamine S/A. Such cortical hypofunction may be relevant and cause a maladaptive response when the system is challenged: in fact, we have recently shown that acute stress dysregulates the glutamate synapse in the mPFC of cocaine-treated rats [17], which were characterized by reduced expression of PSD-95 in the mPFC [18]. The reduced cortical NMDA-mediated tone is strengthened by the reduced expression of metabotropic receptor mGluR5, contributing to delineate an overall picture of cortical hypoglutamatergia as a critical component of long-term ketamine S/A: notably, reduced cortical expression of mGluR5 may be suggestive of relapse liability [19] as well as of reduced ability to extinguish cocaine-seeking [20].…”
Section: Discussionmentioning
confidence: 70%
“…In rats, postnatally exposed to cocaine, GR expression in the medial prefrontal cortex but not plasmacorticosterone levels were increased after short‐term withdrawal, suggesting a dysregulation in the GR system and plastic changes in the developing brain (Caffino et al . ). After 24 days of cocaine self‐administration, rats showed significant lower GR protein expression in the dorsomedial hypothalamus, including the paraventricular nucleus (Mantsch et al .…”
Section: Discussionmentioning
confidence: 97%
“…The subsequent increase in responses to GCs could be due to a left shift in the GC dose response curve and/or an increased efficacy, due to increased unliganded GR levels. This mechanism appears to be at least in part involved in the priming of GR signalling by cocaine in rats, which exhibited increased GR mRNA and protein levels, via an unknown mechanism (Caffino et al, 2015). These authors also however showed increased GR phosphorylation at Ser-232 (the rat equivalent to hGR Ser-211), accumulation of nuclear GR and an increase in expression of the GR steroid receptor coactivator-1 (SRC-1) in the prefrontal cortex of rats three days after cocaine administration.…”
Section: Glucocorticoid-independent Sensitizing Of Gr Signallingmentioning
confidence: 99%